Bibliometric Analysis: Research Trends of Raspberry Pi-Based Egg Incubators in the Last Ten Years (2013-2022) - Yantidewi, Meta; Wati, Jhulinda Nizar; Deta, Utama Alan (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Technological developments that continue to increase provide an impetus for scientists to conduct research,Â  One of them is the field of animal husbandry and instrumentation by making Raspberry Pi-based egg incubators. A device that replicates an incubator by keeping eggs at the right humidity uses a Raspberry Pi microcontroller to incubate the eggs. This research objective is to find out how far the development of the number of international publications using the Google Scholar database and to find out the development map of international research publications based on keywords. Data collection by searching Google Scholar with the keywords "Egg Incubator Raspberry pi", "Egg Incubator IoT" in 2013â€“2022. Trends in the development of international publications analyzed using software in the form of VOSviewer. From the bibliometric analysis carried out, it was found that the system, egg incubator, Raspberry pi, and IoT continues to dominate research on "Egg incubator Raspberry pi". The research will focus on controlling temperature and humidity which is systematized by IoT-based Android to save time, effort and cost. The research results obtained by Bibliometric analysis are not too dominant so that there is still an opportunity to continue research in literature review and become future innovations.